Assessment of Low-density Lipoprotein Cholesterol Levels and Non-invasive Vascular Health in School-aged Children: A Study in Ogasa District, Shizuoka Prefecture - Hasegawa, Nanaho; Iwashima, Satoru; Furusawa, Yuri; Hayakawa, Akinari; Katuki, Junichiro; Hayano, Satoshi; Seki, Keigo; Yata, Soichiro; Kinjo, Kenichi; Sano, Shinichiro (Journal of Atherosclerosis and Thrombosis, 2025)
Aim: The present study assessed low-density lipoprotein cholesterol (LDL-C) levels in school-aged children from the Ogasa District of Shizuoka Prefecture and evaluated the utility of non-invasive vascular tests, namely flow-mediated dilation (FMD) and intima-media thickness (IMT), in pediatric patients with familial hypercholesterolemia (FH).Method: We analyzed the lipid test results of 8,568 students screened for prevention of lifestyle-related diseases and 78 children under 15 years old with cholesterol levels exceeding 220 mg/dL who visited Chutoen General Medical Center. We examined the LDL-C distribution from school-age screenings and conducted FMD and IMT assessments on those meeting the 2022 Pediatric FH Guidelines criteria.Results: Among the screened students, 186 (2.2%) exhibited LDL-C levels above 140 mg/dL, including 123 fourth-graders (2.8%) and 63 first-year junior high students (1.5%). The mean LDL-C level across all students was 90.0 mg/dL (standard deviation: 21.3 mg/dL), with the 95th percentile at approximately 125.0 mg/dL. Of the 78 children who visited the hospital, 65 met the FH diagnostic criteria. In children ≥ 10 years old, no significant IMT differences were observed between the Definitive and Probable FH groups and the Possible FH group; however, a significant difference in the FMD percentage was noted between these groups (9.9% [8.1%-11.9%] vs. 14.2% [11.6%-16.3%], P=0.003).Conclusions: Our findings highlight the LDL-C distribution in FH screening and suggest a potential reduction in FMD in pediatric FH patients ≥ 10 years old. These results emphasize the importance of initiating pharmacological interventions in school-aged children to maintain optimal LDL-C levels for lifelong cardiovascular health.